2016
DOI: 10.1634/theoncologist.2015-0396
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluating Progression in an Era of Progress: A Review of First- and Second-Line Treatment Options in Anaplastic Lymphoma Kinase-Positive Non-Small Cell Lung Cancer

Abstract: The advent of crizotinib, the first small molecule inhibitor against anaplastic lymphoma kinase (ALK), has led to impressive advances in the care of patients with advanced ALK‐rearranged non‐small cell lung cancer. The development of second‐generation ALK inhibitors, starting with the recent U.S. Food and Drug Administration approval of ceritinib, promises to expand the therapeutic landscape for this cohort of patients. With increasing use of molecularly targeted therapy options, it has been observed that dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…[3][4][5] Most crizotinibtreated patients with ALK-positive NSCLC eventually experience progression, because of acquired changes in the dominant biology of the cancer, poor CNS drug penetration resulting in CNS progression, or both. [6][7][8] Mechanisms of acquired resistance to crizotinib typically involve changes in the ALK gene or activation of signaling pathways that bypass ALK. [9][10][11] Second-generation ALK inhibitors currently approved in the postcrizotinib setting, ceritinib and alectinib, have been associated with a median PFS of 5.7 to 6.9 months 12-14 and 8.1 to 8.9 months, 15,16 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Most crizotinibtreated patients with ALK-positive NSCLC eventually experience progression, because of acquired changes in the dominant biology of the cancer, poor CNS drug penetration resulting in CNS progression, or both. [6][7][8] Mechanisms of acquired resistance to crizotinib typically involve changes in the ALK gene or activation of signaling pathways that bypass ALK. [9][10][11] Second-generation ALK inhibitors currently approved in the postcrizotinib setting, ceritinib and alectinib, have been associated with a median PFS of 5.7 to 6.9 months 12-14 and 8.1 to 8.9 months, 15,16 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While most patients develop systemic, multisite progression requiring a change in systemic therapy, a subset of patients develop progression limited to only one or a few anatomic sites, with the remaining disease sites continuing to be controlled by the TKI. This phenomenon has been termed “oligoprogression” (155, 156). In the case of oligoprogressive disease, local ablative therapy (LAT) using surgery or radiation may serve as a strategy that offers several advantages (Figure 4).…”
Section: Developing Strategies To Overcome Resistancementioning
confidence: 99%
“…This phenomenon may be due in part to poor blood-brain barrier penetration of targeted agents and a predilection of EGFR-mutated or ALK-positive NSCLC for the CNS. 66,67 In a study of 100 patients with advanced EGFR-mutant NSCLC treated with gefitinib or erlotinib (including 19 patients with brain metastases at the time of diagnosis), the 2-year cumulative risk of CNS progression was 19%. 68 Another study of 232 patients treated with gefitinib or erlotinib showed that the site of first disease progression was the CNS in 37 patients (16%).…”
Section: Use Of Lat For Oligoprogressive Diseasementioning
confidence: 99%